Analysis of the application of critical chain project management in the product development process and portfolio management of an aircraft manufacturer - De Souza, Fernando Bernardi [UNESP]; De Moraes, Antonio Augusto Cerati [UNESP] (FapUNIFESP (SciELO), 2016)
Products portfolio management, as a part of a product development process, presents challenges as the products life cycle of many sectors, has been continuously diminished. Though several academic studies support the thesis that the Critical Chain Project Management (CCPM) method tends to bring good results in multi-project management, most of these studies do not focus on product development environments and, more specifically, the way in which CCPM endorses product portfolio management in these environments. This perception proves interesting when considering that some scientific studies show the difficulties of an effective portfolio management. This work aimed to study the CCPM application as a support method in the product development process in general, and for portfolio management specifically, seeking to verify, by means of a case study, its forms of application in a company with formal product development processes. The results lead to the conclusion that CCPM is relatively beneficial to the projects performance, contributing both to the product development and product portfolio management.
Keywords: Critical chain; Product development process; Product portfolio management